Clinico-epidemiological profile of early cases of Covid-19 in state of Haryana, India - Chayal, Vinod; Yadav, Rohtas K; Verma, Ramesh; Kalhan, Meenakshi; Nadda, Anuradha; Goswami, Shweta; Dhaka, Rohit; Agrawal, Ginni; Kumar, Gopal; Sachdewa, Aman; et al. (Indian Journal of Community Health, 2021)
Background: Covid -19 disease is caused by novel coronavirus known as SARS CoV 2. Coronaviruses are known to cause disease in humans which can be a common cold or a serious pneumonia. SARS Cov 2 is a new variant of coronavirus which was never reported in humans before detection of cluster of cases of pneumonia in Wuhan on 31st December, 2019.Objective: The study was conducted with the objective to find out clinico- epidemiological profiles of early Covid-19 patients in state of Haryana, India and to find out knowledge about covid appropriate behaviors among covid 19 patients. Methods: All the covid-19 cases in the five districts of Haryana were enumerated from March 2020 to May 2020. These Covid-19 cases were contacted telephonically and those who gave their consent to participate in the study were asked to fill interview schedule. Observations: There were 356 covid cases reported in five districts attached to PGIMS, Rohtak. Out of total,254 subjects participated in the study, there were 60.6 % males and 39.4% females who participated in the study. Blood groups of all the participants were also enquired and it was observed that B +ve was most common (19.7%) blood group followed by A+ve (16.5%) and O +ve (15.7%). Conclusion: It can be concluded by the study that majority of the subjects were males, overweight and blood group A & B were the most common blood groups. It was observed that 75.2 % participants were aware about the use of mask, social distancing, hand hygiene and cough etiquettes.